Occupational risk assessment and selected morbidities among cement brick unit workers in a rural area of Bangalore District, India - Sunny, Sobin; Fathima, Farah Naaz; Joy, Jiss; Passah, Benjamin Leroy; Thomas, John Chiramel; Agrawal, Twinkle (International Journal of Occupational Safety and Health, 2022)
Introduction: The labor-intensive nature of cement brick manufacturing, its unorganized nature and internal migration, expose the employees to several occupational health hazards. The objective of the study was to assess the occupational risks in cement brick unit settings and to estimate the prevalence of respiratory and musculoskeletal morbidities among the cement brick unit workers in a rural area of Bangalore urban district. Methods: A cross-sectional study was conducted among cement brick unit workers over two months. A semi-structured questionnaire was used to capture sociodemographic details. Multiple observations on the field and the World Health Organization semi-quantitative risk assessment matrix were used to obtain risk scores of the occupational hazards. A structured questionnaire on respiratory symptoms and Minispir Portable Spirometer were used to assess the respiratory morbidities and lung functions. Musculoskeletal morbidities were assessed using the Modified Nordic questionnaire. Proportions were used to describe respiratory and musculoskeletal morbidities. Chi-square test, Fisher’s exact test and multivariate logistic regressions were done to identify significant variables. Results: Among 120 subjects, 110 (91.6%) were men and 85.8% were migrants. Injury due to falls of heavy objects, back injury, respiratory complaints and slips/falls were found to be high-risk health hazards. The prevalence of respiratory morbidity was 21.7% and that of musculoskeletal morbidity was 51.7%. Workers receiving a higher salary (≥ 1500 Indian rupees) had higher odds of having respiratory morbidity. Conclusion: The prevalence of respiratory and musculoskeletal morbidities was high. Introduction of mechanical equipment, decreasing work hours, periodic medical examinations and appropriate use of personal protective equipment will help in risk reduction as per this study.